Why fix it if it's not broken! The role of audiologists in families of hearing children born to deaf parents. (3rd July 2018) - Moroe, Nomfundo
Abstract: Background: The Health Professions Council of South Africa (HPCSA) clearly states the role of audiologists in the management of children diagnosed with hearing loss. However, there are no outlined guidelines regarding the role of audiologists in hearing Children of Deaf Adults (CODAs). A literature search on the role of audiologists in this population yielded no results both locally and internationally. Objectives: This study seeks to understand the role of audiologists in Deaf parented families as perceived by CODAs. Methods: Ten CODAs aged between 21 and 40 were recruited through purposive and snowball sampling. Data were collected through qualitative, semi-structured interviews. Data were inductively analyzed through thematic analysis. Results: The findings revealed mixed feelings. Some participants indicated their need for audiological services while others perceived audiologists as wanting to fix something that is not broken. Furthermore, most participants indicated not needing any support services while the involvement of extended family was met with mixed feelings. Conclusions: There is, therefore, a need for audiologists to critically scrutinize and define their role and its boundaries in these families. This can be achieved by engaging in a frank and honest discussion between audiologists and Deaf-parented families.